2021
DOI: 10.1038/s41588-020-00751-5
|View full text |Cite
|
Sign up to set email alerts
|

A cross-platform approach identifies genetic regulators of human metabolism and health

Abstract: In cross-platform analyses of 174 metabolites we identify 499 associations (p<4.9×10 -10 ) characterized by pleiotropy, allelic heterogeneity, large and non-linear effects, and enrichment for nonsynonymous variation. We identify a signal at GLP2R (p.Asp470Asn) shared between higher citrulline levels, body mass index, fasting glucose-dependent insulinotropic peptide and type 2 diabetes, with beta-arrestin signalling as the underlying mechanism. Genetically-higher serine levels are shown to reduce the likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
176
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 129 publications
(194 citation statements)
references
References 58 publications
6
176
0
Order By: Relevance
“…Prior studies examined lipid phenotypes that were mixtures of similar, but distinct species; lacked structural characterization of lipid species; or were contaminated through isotopic overlap. Many of the associations between lipid species and prototypical lipid regulating genes observed in our study -such as FADS1/FADS2, APOE and LDLR -have been reported in earlier GWAS [7][8][9][10][11][12][13][14][15]17,23 . With our expanded lipidomic profile, we have built on these earlier studies, identifying many new loci associated with lipid species and classes.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Prior studies examined lipid phenotypes that were mixtures of similar, but distinct species; lacked structural characterization of lipid species; or were contaminated through isotopic overlap. Many of the associations between lipid species and prototypical lipid regulating genes observed in our study -such as FADS1/FADS2, APOE and LDLR -have been reported in earlier GWAS [7][8][9][10][11][12][13][14][15]17,23 . With our expanded lipidomic profile, we have built on these earlier studies, identifying many new loci associated with lipid species and classes.…”
Section: Discussionsupporting
confidence: 70%
“…Our high resolution genome-wide association analyses of the human lipidome has identified 737 independent genomic regions associated with lipid metabolism, of which 509 represent novel genetic loci. This is a substantial increase over previous studies with similar or larger sample sizes 7,10,23 . Our expanded lipidomic platform utilises extensive chromatographic separation to increase the diversity of measured lipid species and distinguish lipid isomers and isotopes over those measured in previous studies.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Large scale research consortia studying genetic and metabolite markers have given us insight into underlying pathways involved in type 2 diabetes development (4, 5). Given the ability of miRNAs to target thousands of genes, miRNAs are likely also to play a regulatory role in the metabolic disturbance that causes type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%